KESANTUNAN BERBAHASA PEJABAT LEGISLATIF/TOKOH PARTAI TINGKAT KABUPATEN DI SUMATRA BARAT DALAM MEDIA SOSIAL - Niswasani, Niswasani; Juita, Novia (Jurnal Bahasa dan Sastra, 2019)
This study aims to describe language politeness by district level legislative / figure leaders in West Sumatra in Social Media.This type of research is qualitative research because tehe data generated is in the form of qualitative data in the form of descriptions. The research data is in the form of utterances by some district legislative / figure leaders in West Sumatra on social media. The source of this research data is from the screenshots of the district-level legislative / party officials' Facebook speeches in West Sumatra. The technique of validating research data uses detailed description techniques. The findings of this study, found six maxims, namely the (1) maxim of wisdom, (2) maxim of acceptance, (3) maxim of mercy, (4) maxim of humility, (5) maxim of compatibility, and (6) maxim of sympathy. Of the six maxims, it was found that obeying the most dominant was the maxim of conclusions and the most dominant violation was the maximal match.Keywords: language politeness, legislative officials/party figure,facebook